Comparative Analysis of Optimal Stock Portfolio Results using The Markowitz Method and a Single Index (Study on LQ 45 Company Shares Listed on the Indonesia Stock Exchange Period January – December 2024) - Matdio Siahaan; Jhonni Sinaga; David Pangaribuan (Greenation International Journal of Economics and Accounting, 2026)
In the era of digital technology advancement, Indonesia has become an alternative investment destination in the capital market, attracting global attention. Investing in the capital market offers high returns and significant risks. Therefore, investors need strategic skills to mitigate risk. Risk reduction can be achieved through asset diversification, also known as portfolio formation. This study aims to develop an optimal portfolio using the Markowitz Single Index method and to determine the optimal investment proportion for the LQ45 Index. The sample used was the LQ45 index members from January 2024 to December 2024. This method is a comparative study with daily data, using calculations of realized return, variance, covariance, and cut-off rate for a single index. The analysis using the Markowitz method resulted in seven stocks as optimal portfolio recommendations, the stock composition is different between the two methods with a return of 0.15% and a risk of 1.25%. The analysis using the Single Index method resulted in seven stocks as optimal portfolio recommendations, with a return of 0.037% and a risk of 0.07%.